EFEK PAPARAN KRONIK CADMIUM CHLORIDE (CdCl2) DOSIS RENDAH TERHADAP HIPERPLASIA LAMELA SEKUNDER INSANG DAN NEKROSIS SEL TUBULUS PROKSIMAL GINJAL IKAN ZEBRA DEWASA (Danio rerio) - Evilya Fitra Indriana; Rio Risandiansyah; Noer Aini (Jurnal Kedokteran Komunitas, 2020)
Introduction: Cadmium (Cd) is a toxic heavy metal, and can water soluble. Chronic low-dose exposure of the metal causes disturbances on the respiratory system and kidneys. In adult zebrafish the toxic effect causes hyperplasia gill and necrotic nuclei of kidney cell in adult fish. This research studies the effect of chronic toxicity of CdCl2 on secondary lamella of gills and kidney cell nucleus in zebrafish  exposed to CdCl2 since juvenile phase to adulthood.Methods: Juvenile zebrafish (Danio rerio), age 3 months, were divided into 4 groups, namely the control group, 3 groups receiving CdCl2 dose of 0,5 ppm, 1 ppm, and 1,5 ppm respectively, for 30 days. Hiperplasia secondary lamella of gills and necrotic nuclei of kidney cells were histologically observed. Prior to the observations the gill and kidney were stained by HE. Secondary lamella gill data were tested by One-Way Anova followed by Post Hoc Tests, data of renal proximal tubular cell nuclei necrosis was tested by Kruskal Wallis followed by Mann Whittney test (p <0.05).Results: Exposure to CdCl2 doses of 0,5 ppm, 1 ppm, and 1,5 ppm significantly increased the amount of hyperplasia secondary lamella of the gills by 67%, 78%, and 86% respectively compared to those of the control group. Exposure to CdCl2 doses of 0.5 ppm, 1 ppm, and 1.5 ppm significantly increased the core necrosis of kidney cells nucleus in adult zebrafish 75%, 79%, and 84% compared to the control group.Conclusion: Exposure to CdCl2 doses of 0.5 ppm, 1 ppm, and 1.5 ppm increases the number of hyperplasia secondary lamella of gills and necrotic nuclei of kidney cells adult zebrafish.Keywords: Cadmium chloride (CdCl2), secondary lamella hyperplasia of gills, kidney cell nucleus necrosis, adult zebrafish.